1985
DOI: 10.1038/bjc.1985.96
|View full text |Cite
|
Sign up to set email alerts
|

Monoclonal antibody assay of serum placental alkaline phosphatase in the monitoring of testicular tumours

Abstract: These data demonstrate that determination of PLAP levels using this sensitive immunoassay is an important new adjunct in the monitoring of the response to treatment in patients with seminomaa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…Lactate dehydrogenase levels correlate roughly with the amount of tumour present but the enzyme is in no way a specific monitor of disease activity. Placental alkaline phosphatase, particularly when detected using the monoclonal antibody H17E2, may prove a useful marker for seminoma but raised marker levels in patients who smoke cloud the issue Epenetos et al, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…Lactate dehydrogenase levels correlate roughly with the amount of tumour present but the enzyme is in no way a specific monitor of disease activity. Placental alkaline phosphatase, particularly when detected using the monoclonal antibody H17E2, may prove a useful marker for seminoma but raised marker levels in patients who smoke cloud the issue Epenetos et al, 1985).…”
Section: Methodsmentioning
confidence: 99%
“…At one time PLAP looked promising (Epenetos et al, 1985) but this initial promise has not been fulfilled (Nielsen et al, 1990). The question then arises: might the combination of PLAP, LD, and P HCG prove more useful in the assessment of seminoma than simple consideration of individual markers?…”
Section: Discussionmentioning
confidence: 99%
“…Increased levels of lactate dehydrogenase (LD) may be found in patients with seminoma but this enzyme cannot be considered specific (Taylor et al, 1986;von Eyben et al, 1988;Fossa & Fossa, 1989). A heat-stable alkaline phosphatase isoenzyme, placental alkaline phosphatase (PLAP), has been suggested as a potential marker for seminoma (Epenetos et al, 1985;De Broe & Pollet, 1988) but we have recently shown that, considered alone, its clinical usefulness is limited (Nielsen et al, 1990). PLAP is elevated in healthy smokers and this further complicates its use as a marker for seminoma.…”
mentioning
confidence: 99%
“…We have attempted immunocytology on cervical smears using both H317 and H17-E2 in an indirect immunoperoxidase staining technique; however, no clear differences were noted between normal or abnormal cervix. The high levels of cervical tissue PLAP and PLAP-like AP activities suggest a potential as targets for radioimmunolocalisation of invasive and metastatic disease, as has been performed successfully in ovarian and testicular cancer (Epenetos et al, 1985b;Critchley et al, 1986), or for determining the extent of lymphatic spread by lymphangiography as has been attempted in cervical cancer using the HMFG2 mAb (Epenetos, 1985).…”
Section: Cervical Swabsmentioning
confidence: 99%